Affective computing in a T-Learning application - Baldassarri, Rosa (2012)
This paper presents T-EDUCO, the first t-learning affective aware tutoring tool. T-EDUCO goes further than simply broadcasting an interactive educational application by allowing the figure of a tutor to be present and to govern the students’ learning process. The tutor can access academic and emotional information about the students through a continuous “emotional path” that includes timestamps and information about the progress made in each exercise. In this way, personal messages or extra educational contents for improving learning can be sent to the students. All this is made possible by a combination of broadcast and broadband technologies